SHORT PULSE LASER GENERATION USING PHASE SHIFTED FIBER BRAGG GRATING - Kbashi, Hani; Al-Naimee, Kais; Taleb, A. (Iraqi Journal of Science, 2024)
Short pulse laser generation using phase shifted fiber Bragg grating (FBG) is a theoretical demonstration and investigation in this paper. The specified refractive index can be photo-written in an optical fiber using UV laser with a standard phas mask scanning techniques. Two Bragg gratings were specially designed to spectrally filtering the edges of the input puise. When the FBGs are fabricated in the core of the optical fiber, most of the power travels in the core with a smock part corresponding to the evanescent wave that travels outside near the core in the cladding. The results show the desired full width at half maximum (FWHM) of the pulse propagation in the core of the optical fiber is 5,025 nm, which corresponds to frequency FWHM equal to 6.27*10". The duration bandwidth product of theoretical pulse using autocorrelation track was 0.65, and then the controllable pulse width generated using this method approximately equal to Ipsec